Kontribusi Daya Ledak Otot Tungkai dan Kelenturan Pinggang terhadap Ketepatan Smash Bolavoli - Dini Hidayatul Qudsi; Sayuti Syahara; Hendri Irawadi; Yogi Setiawan (Jurnal Patriot, 2021)
The problem in this research is that there is still a lack of smash accuracy on male volleyball players at SMA N 8 Padang. This study aims to determine the contribution between the explosive power of the leg muscles and the flexibility of the waist muscles on the smash accuracy of male volleyball players at SMA N 8 Padang. This research is a correlational type, with a population of this study as many as 20 male players. Sampling was done by saturated sampling, so the sample in this study were 20 male volleyball players at SMA N 8 Padang. The explosive power of the leg muscles was measured by the vertical jump test and the flexibility of the waist muscles by the bridge test, then the accuracy of the volleyball smash was measured by a normal smash. The data analysis technique used was simple correlation analysis and multiple correlation. Results: There was a contribution of the leg muscle explosive power to the accuracy of the volleyball smash of 50.27%. There is a contribution of waist muscle flexibility to the accuracy of the volleyball smash of 43.43%. Then, the leg muscle explosive power and the flexibility of the waist muscles simultaneously contributed to the accuracy of the volleyball smash by 72.93%. Thus, it can be concluded that the leg muscle explosive power and flexibility of the waist contribute to the accuracy of the volleyball smash.